ARGON RELEASE MECHANISMS OF BIOTITE IN VACUO AND THE ROLE OF SHORT-CIRCUIT DIFFUSION AND RECOIL - Lo C.H.; Lee J.K.W.; Onstott T.C. (My University, 2000)
Understanding argon release mechanisms in K-bearing minerals is essential in interpreting the 40Ar/39Ar data and their application to geological studies. The release mechanisms of argon in vacuo have been examined in a series of 40Ar/39Ar isothermal heating experiments on two biotite specimens with Fe/(Fe+Mg) (Fe#)=0.50 and 0.87 respectively. The crystal structure of the biotite was also monitored during in vacuo heating by an in-situ high temperature X-ray diffractometer (HTXRD), and also examined by scanning electron microscopy (SEM). At temperatures greater than 600°C, argon release is mainly controlled by the structural decomposition of the biotite crystal arising from oxidation and dehydroxylation, whereas at temperatures less than 600°C, argon release appears to be controlled by a multipath-diffusion mechanism, with effective D/a2 values about 2-4 orders of magnitude higher than those extrapolated from hydrothermal data. Both the argon diffusivity and Ar release patterns are strongly related to biotite composition, in which the Fe-rich biotite has a higher argon diffusivity and degasses at lower temperatures than the Mg-rich biotite. Unless contaminated by other phases, biotites will tend to yield flat age spectra for temperature steps higher than 600°C, regardless of the initial distribution of argon isotopes in the crystal structure, since the argon released at T>600°C is strongly correlated with the decomposition process. At temperature steps lower than 600°C, however, biotite age spectra can exhibit discordant dates since the gas release is controlled mainly by defect-enhanced (short-circuit) diffusion mechanisms. Consequently, models using such low-T steps with the intent of extracting information on the spatial distribution of Ar will not lead to accurate interpretations of geologic histories, unless the potential effects of short-circuit diffusion are well-constrained.
Keywords: GEOCHRONOLOGY; ARGON; DIFFUSION; BIOTITE